EFEKTIVITAS PENGAWASAN METROLOGI LEGAL OLEH DINAS PERDAGANGAN DAN PERINDUSTRIAN KOTA PEKANBARU (Studi Kasus Pada Standarisasi Alat Ukur Stasiun Pengisian Bahan Bakar Umum) - Putra, Yogie Pratama; Yuliani, Febri (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2021)
Legal Metrology is a metrology that manages units of measure, measurement methods and measuring instruments, which involve technical and regulatory requirements based on the Act which aims to protect the public interest in terms of the correctness of measurements. The purpose of this study is to describe the effectiveness of legal metrology supervision by the Department Trade and Industry of Pekanbaru City (case study on standardization of measuring instruments for public fueling stations) and to determine the inhibiting factors for the effectiveness of legal metrology supervision by the Department of Trade and IndustryÂ  Pekanbaru City Industry (Case Study on Standardization of General Fuel Filling Measuring Instruments). The theory used in this study is the theory of effectiveness of supervision from Sarwoto which is measured in seven indicators, namely elements of accuracy, timely, objective and comprehensive, centralized, economically realistic, organizationally realistic and flexible. The method that the researcher uses is a qualitative method using a descriptive approach. In this qualitative research, the author analyzes on the basis of research problems using data collection techniques in the form of interviews, observations and documentation. The results of this study indicate that the effectiveness of legal metrology supervision by the Department of Trade and Industry of Pekanbaru City (a case study on the standardization of measuring instruments for public fueling stations) can be seen from the seven elements of indicators of accuracy, timely, objective and comprehensive, centralized, economically realistic, organizationally realistic and flexible has not run effectively. The obstacle to this supervision is the need to improve coordination between parties and the need to pay attention to all existing policies.Â Keywords: Effectiveness, Supervision, and Legal MetrologyÂ